Schriften über Bildung und Kulturpolitik in der Monatsschrift für Deutsch-Ungarischen Kulturaustausch der Ungarisch-Deutschen Gesellschaft in Budapest (1940–1944) - Niklai, Patrícia Dominika (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
Between 1940 and 1944 (and even earlier, in the 1930‘s), the Hungarian cultural and educational policy focused on Christian national ideology and Hungarian cultural superiority. Hungarian writers also highlighted this ideology in addition to emphasizing the importance and benefits of the bond with Germany. These manifested and mingled in a pro-German spirit based on the current political alliances. In the following this will be examined through the writings of Hungarian authors, who considered that the bond between the Hungarians and the Germans has different natural historical roots. In this article several writings were selected about education and cultural policy from the monthly journal for German-Hungarian cultural exchange of the Hungarian-German Society in Budapest. On this basis, an overview of the spirit of the age will be given here using the writings of Hungarian authors published in German. Other periodicals of that era were also researched – such as the Journal of Eastern European Law, Journal of the Academy of German Law, Hungarian Yearbooks between 1933–1943 – but they also do not contain so many writings on the topics of education and cultural policy, which is why the monthly journal for German-Hungarian cultural exchange was chosen as the title and focus point of this study.